MODEL KEPEMIMPINAN KEPALA SEKOLAH DALAM PENGEMBANGAN BUDAYA RELIGIUS DI SMA NEGERI 1 MENTAYA HILIR SELATAN KABUPATEN KOTAWARINGIN TIMUR - malisi, ali sibram (GRADUATE SCHOOL OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2017)
The Principal leadership model is a core factor in the development of the religious culture. The school is one of the Model School of Iman and taqwa schools. Thus, it interested to be researched about the Principal leadership model in developing the religious culture in the school. This article focused on namely (1) the principal developed the religious culture through two leaderships models namely; (a) Situational leadership model is when a principal assigning works according to each expertise. This means that the headmaster must be good at reading the situation and condition to each educator and the staff. And thus, each one does the better and responsible works, (b) transformational leadership model is a model providing priority to the opportunity and encouraging all workers of the school in order to wok in the sublime values. And thus, all the staffs do not get insisted in optimally participating to achieve the ideal goals in the school. (2) the used strategies are namely; (a) appling the religious practise to be inured as a habit, (b) providing exemplary by doing to relate alttitude and behaviour in a day, (c) integrating the common subjects to the islamic subjects, (d) developing the islamic extracurricular activity that is through the Osis Programmings.There were discovered that the majority ones appreciate the minority ones. Meanwhile, the minority ones respect the majority ones. And thus, it is able to build the harmonious and religious atmospheres in the school. Keyword : Principal Leadership Model, Religious Culture.